AI-based analysis of surgical outcomes in vitrectomy with and without cystotomy for refractory cystoid diabetic macular edema - Mizuho Mitamura; Michiyuki Saito; Kiriko Nishiyama-Hirooka; Zhenyu Dong; Ryo Ando; Satoru Kase; Susumu Ishida (Scientific Reports)
Abstract The aim of this study was to compare surgical outcomes in vitrectomy with and without cystotomy for refractory cystoid diabetic macular edema (DME). This study enrolled 35 eyes of 29 patients who underwent vitrectomy for refractory DME. The eyes were divided into 2 groups, those undergoing vitrectomy with cystotomy (cystotomy group) (n = 8) and vitrectomy with internal limiting membrane (ILM) peeling only (ILM peeling group) (n = 27). The endpoints were central retinal thickness (CRT), best-corrected visual acuity (BCVA), macular fluid (MF) area. The MF area was determined and measured using a semantic segmentation model “Hokkaido University MF segmentation model” and subdivided into inner MF (IMF) area bounded by the inner nuclear layer (INL), and outer MF (OMF) area between the outer border of INL and ellipsoid zone. The cystotomy group showed a significant reduction in CRT at 1 month postoperatively compared to the ILM peeling group (P < 0.05). The cystotomy group preserved BCVA at 6 months postoperatively compared to preoperatively. There was a significant difference between the cystotomy and the ILM peeling groups in the reduction of the OMF area at 1 month postoperatively (P < 0.01). Cystotomy for refractory DME was more effective in reducing the OMF area.